THE BIBLE'S VIEWPOINT OF THE BIBLE'S VIEWPOINT - Kodirova Surayyo Karshibaevna (Western European Studies, 2023)
This scientific article presents ways to solve global problems by promoting students-students studying in educational institutions through extracurricular activities such as environmental culture, environmental literacy and environmental competence.
Keywords: pedagogical; extracurricular; solve